1995
DOI: 10.1017/s0022215100129998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between short-term and long-term post-operative evaluation of sleep apnoea after uvulopalatopharyngoplasty

Abstract: For a long time uvulopalatopharyngoplasty (UPPP) has been used to treat the obstructive sleep apnoea syndrome (OSAS). The diverse surgical effects, the inadequate understanding of operation effect consistency, the possibility of disease progression, and the few reported papers for long-term evaluation after UPPP aroused our interest in designing this study. Fifteen OSAS patients who had undergone UPPP with pre-operative, initial post-operative and long-term post-operative polysomnographic studies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 21 publications
1
40
0
5
Order By: Relevance
“…This may indicate that better selection of cases using intraluminal upper airway pressure recording results in a better success rate among OSAS patients. The lower success rate among the second group can be due to the presence of multisegmental resistance of the upper airway (14), persistence of the central element in some patients with mixed sleep apnea; some uncooperative patients did not follow the diet regime and others may be in need of adjuvant maxillofacial corrective surgery.…”
Section: Resultsmentioning
confidence: 99%
“…This may indicate that better selection of cases using intraluminal upper airway pressure recording results in a better success rate among OSAS patients. The lower success rate among the second group can be due to the presence of multisegmental resistance of the upper airway (14), persistence of the central element in some patients with mixed sleep apnea; some uncooperative patients did not follow the diet regime and others may be in need of adjuvant maxillofacial corrective surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting data were reported concerning the effect of UPPP on daytime sleepiness in OSA. Whereas Janson et al [27] and Lu et al [28] reported an improvement in daytime sleepiness of 68 and 80%, respectively, persistence of daytime somnolence was found in 75% of the patients reported by Hagert et al [29]. However, these studies are difficult to compare, because different scoring systems were used to measure hypersomnolence.…”
Section: Discussionmentioning
confidence: 98%
“…Three research groups included selected patients [7,31,62], while the other three treated unselected patients [36,43,46]. -There were differences in surgical method.…”
Section: Adenotonsillectomy In Childhoodmentioning
confidence: 99%